Effect and Mechanisms of State Boredom on Consumers’ Livestreaming Addiction - Zhang, Nan; Li, Jian (Frontiers in Psychology, 2022)
With the rapid development of livestreaming marketing in China, consumers spend an increasing amount of time watching and purchasing on the platform, which shows a trend of livestreaming addiction. In the early stage of the COVID-19 pandemic, the addiction exacerbated by a surge of boredom caused by home quarantine. Based on the observation of this phenomenon, this research focused on whether state boredom could facilitate consumers’ livestreaming addiction and explored the associated mechanisms of this relationship. Based on three studies, this research found that state boredom had a positive effect on consumers’ livestreaming addiction, and this relationship worked through the mediating effect of consumers’ sensation seeking. We further verified a moderated mediation effect of consumers’ life meaning perception, where the indirect effect of state boredom on consumers’ livestreaming addiction via consumers’ sensation seeking existed for high and low levels of life meaning perception, but in opposite directions. The conclusions provided theoretical and practical implications of livestreaming marketing and healthy leisure consumption.